2019
DOI: 10.18632/oncotarget.26999
|View full text |Cite
|
Sign up to set email alerts
|

Somatic molecular analysis augments cytologic evaluation of pancreatic cyst fluids as a diagnostic tool

Abstract: Objective: Better tools are needed for early diagnosis and classification of pancreatic cystic lesions (PCL) to trigger intervention before neoplastic precursor lesions progress to adenocarcinoma. We evaluated the capacity of molecular analysis to improve the accuracy of cytologic diagnosis for PCL with an emphasis on non-diagnostic/negative specimens. Design: In a span of 7 years, at a tertiary care hospital, 318 PCL endoscopic ultrasound-guided fine needle aspirations (EUS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 50 publications
(60 reference statements)
0
12
0
Order By: Relevance
“…Whereas the presence of KRAS mutations supports the diagnosis of a mucinous over a non-mucinous cyst, GNAS mutations favor the diagnosis of IPMN over MCN [ 25 , 29 , 65 , 66 , 76 , 79 ]. Evidence suggests that NGS has higher sensitivity than cytology or elevated cystic fluid CEA levels [ 25 , 48 , 52 , 68 ], whereas the combination of cytology, high CEA levels and NGS has shown the highest diagnostic accuracy to detect neoplastic mucinous cysts [ 48 ]. In addition, the presence of specific mutations—such as the ones in the SMAD4, TP53, CDKN2A, or NOTCH1 genes—have been linked with high-risk cysts [ 25 , 76 , 87 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas the presence of KRAS mutations supports the diagnosis of a mucinous over a non-mucinous cyst, GNAS mutations favor the diagnosis of IPMN over MCN [ 25 , 29 , 65 , 66 , 76 , 79 ]. Evidence suggests that NGS has higher sensitivity than cytology or elevated cystic fluid CEA levels [ 25 , 48 , 52 , 68 ], whereas the combination of cytology, high CEA levels and NGS has shown the highest diagnostic accuracy to detect neoplastic mucinous cysts [ 48 ]. In addition, the presence of specific mutations—such as the ones in the SMAD4, TP53, CDKN2A, or NOTCH1 genes—have been linked with high-risk cysts [ 25 , 76 , 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…NGS enhanced the diagnostic accuracy of EUS-FNA cytology to detect neoplastic mucinous cysts and differentiate them from the non-mucinous ones [ 49 ]. Notably, evidence indicated that NGS was more sensitive than the cytologic examination or elevated CEA cystic fluid levels (≥192 ng/mL), which are the two modalities traditionally used to evaluate pancreatic cysts [ 25 , 48 , 52 , 68 ]. For instance, Ren et al showed the combination of cytologic examination, elevated CEA cystic fluid levels, and NGS reached a sensitivity of 94.1% and a specificity of 100% for the detection of neoplastic mucinous cysts [ 48 ].…”
Section: The Role Of Ngs Performed On Pancreatic Small Biopsiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Solid pseudopapillary neoplasms and cystic neuroendocrine neoplasms are notable, rare exceptions, as both are non-mucinous cystic lesions that do have some malignant potential and may require surgical resection. However, mucinous PCLs such as IPMNs and MCNs are generally regarded as precursor lesions for PC [ 8 , 12 , 20 , 21 ]. IPMNs are the most common pre-malignant PCL, being much more common than MCNs.…”
Section: Current Management Of Pclsmentioning
confidence: 99%
“…While the low cellularity of PCL fluid limits cytological yield, biochemical analysis of PCL fluid has proven an important adjunct in characterising PCLs. Cyst fluid CEA has been shown to have a sensitivity of between 59 and 67% and specificity of 83–91% for detection of mucinous cysts, and is among the best of the biomarkers currently available [ 20 , 35 ]. Mutational profiling of patients has shown utility in the characterisation of different PCL subtypes.…”
Section: Current Management Of Pclsmentioning
confidence: 99%